HHV-6B infection, T-cell reconstitution, and graft-vs-host disease after hematopoietic stem cell transplantation. (December 2018) - Phan, Tuan; Pritchett, Joshua; Leifer, Cynthia; Zerr, Danielle; Koelle, David; Di Luca, Dario; Lusso, Paolo
Abstract Successful and sustained CD4+ T-cell reconstitution is associated with increased survival after hematopoietic cell transplantation (HCT), but opportunistic infections may adversely affect the time and extent of immune reconstitution. Human herpesvirus 6B (HHV-6B) efficiently infects CD4+ T cells and utilizes as a receptor CD134 (OX40), a member of the TNF superfamily that antagonizes regulatory T-cell (Treg ) activity. Reactivation of HHV-6B has been associated with aberrant immune reconstitution and acute graft-versus-host disease (aGVHD) after HCT. Given that Treg counts are negatively correlated with aGVHD severity, we postulate that one mechanism for the poor CD4+ T-cell reconstitution observed shortly after transplant may be HHV-6B infection and depletion of peripheral (extra-thymic) CD4+ T cells, including a subpopulation of Treg cells. In turn, this may trigger a series of adverse events resulting in poor clinical outcomes such as severe aGVHD. In addition, recent evidence has linked HHV-6B reactivation with aberrant CD4+ T-cell reconstitution late after transplantation, which may be mediated by a different mechanism, possibly related to central (thymic) suppression of T-cell reconstitution. These observations suggest that aggressive management of HHV-6B reactivation in transplant patients may facilitate CD4+ T-cell reconstitution and improve the quality of life and survival of HCT patients.